2005
DOI: 10.1021/ja051095d
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Effective Charge of TGA-Stabilized CdTe Nanocolloids?

Abstract: The surface charge of semiconductor nanoparticles, Q, is an important parameter which determines their electrokinetic behavior, stability in water and polar solvents, functions of optical and electronic devices, self-assembly properties, and interactions with cell membranes. We have developed a simple method for quantitative determination of Q in their native aqueous environment. The method does not require the knowledge of exact atomic structure or make assumptions about effects of drying on charge distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
(22 reference statements)
2
39
0
Order By: Relevance
“…However, here we used TGA not only as the sulfur source but also as the thiol-capping agent to the sulfide particles' surface. It was reported that, at low pH, thiol was complexed to sulfide particles: in contrast, under an alkaline environment, thiol was more strongly complexed to free metal ions [32,33]. In this experiment, with addition of TGA solution, the pH of the solution was adjusted to 8.…”
Section: Resultsmentioning
confidence: 92%
“…However, here we used TGA not only as the sulfur source but also as the thiol-capping agent to the sulfide particles' surface. It was reported that, at low pH, thiol was complexed to sulfide particles: in contrast, under an alkaline environment, thiol was more strongly complexed to free metal ions [32,33]. In this experiment, with addition of TGA solution, the pH of the solution was adjusted to 8.…”
Section: Resultsmentioning
confidence: 92%
“…In addition to the usual large, and technologically important, spontaneous polarizations in many wurtzite structures, this paper demonstrates that surface terminations are important in determining spontaneous polarizations in nanostructures. In addition, these effects have been estimated at the order-of-magnitude level for spherical quantum dots in view of the growing scientific and technological interests in colloidal quantum dots which have approximately spherical geometries [9][10][11][12]. These results take on enhanced significance in view of recent results on the varying charge states of colloidal nanocrystals [10] as well as theoretical efforts aimed at understanding the polarization states of colloidal nanocrystals [13].…”
Section: Resultsmentioning
confidence: 99%
“…31 At the same time, the carboxylic acid groups of the TGA ligand shell on CdTe NCs create a net negative charge reaching 2 to 10 electrons per particle. 32 This results in a large repulsive force between NCs in their original aqueous solution. Partial removal of TGA stabi lizers from the NC surface due to treatment with methanol reduces the repulsive forces between NCs, causing them to form linear aggregates and later on to fuse into thicker, polycrystalline wires.…”
mentioning
confidence: 99%